Comparative ecology of Pachyptila species breeding sympatrically at Gough Island - Jones, Christopher Warrick Price (Department of Biological Sciences, 2019)
Prions (Pachyptila spp.) are one of the most abundant seabird groups of the Southern Ocean but their taxonomy, at-sea distribution and foraging ecology are poorly known. There has been considerable confusion surrounding the taxonomy of prions and their identification at sea is problematic. Recent studies have confirmed the presence of two very similar prion species breeding sympatrically, approximately three months apart, on Gough Island: Pachyptila vittata and P. macgillivrayi. This discovery raised several questions about the ecological segregation of these species. My thesis compares the breeding distribution, at-sea movements, phenology, foraging ecology and trophic segregation of the two species at Gough Island, and compares Gough birds with the P. vittata from Tristan da Cunha. In 2000/01 it was estimated that 1.5–2.0 million pairs of prions bred on Gough Island, suggesting that this site supports the largest populations of both species in the world. However, the contribution of each species to this total as well as spatial and temporal segregation of the two species required further investigation. To investigate the breeding distribution and relative species proportions across Gough Island, 2227 prion specimens were collected opportunistically over several years at various sites. Most birds were caught at night or found dead, thus only provide an inference of breeding distribution. However, observations of incubating birds at several sites indicate that the data are representative of nesting distributions. At most sites there was evidence for consistent dominance of one or other species, although this need not mean local allopatry; a few P. vittata breed in Prion Cave, where P. macgillivrayi is by far the most abundant species. A few sites had both species in similar proportions, but these tended to be sites with relatively few birds and/or represent areas where the two species’ ranges abut. Weighting each site equally suggested a roughly equal ratio of P. vittata/P. macgillivrayi, but there was little coverage of the northern and eastern glens, where P. vittata appears to predominate. The habitat area occupied by P. macgillivrayi comprises ~40% of Gough Island, suggesting they comprise ~40% of the prion population if the density of breeding birds is roughly similar for both species. Based on these proportions and the previous population estimate, some 600 000 to 1 000 000 P. macgillivrayi and 750 000 to 1 200 000 P. vittata are estimated to breed on Gough Island Additional investigation is required to elucidate the spatial segregation of the two species at a finer scale. Additional detailed categorizing of habitat types is needed to determine the fine-scale drivers for their spatial segregation. The prions’ phenology, foraging ecology and trophic segregation was examined through geolocation technology, salt-water immersion sensors (recording time on the water), stable isotope analyses as well as a comparison of bill morphology. Breeding adults of both species were tagged with geolocators/immersion sensors on Gough Island and breeding adults of P. vittata were tagged at Tristan da Cunha. During their respective breeding seasons P. vittata largely remained within 1500 km to the north-east of the colony and P. macgillivrayi occupied waters within 1000 km to the south of the colony. At Gough Island, P. vittata departed and returned to the colony on average 91±9 days earlier than P. macgillivrayi. The length of the non-breeding period did not differ between species and all tracked individuals except one P. vittata engaged in a pre-laying exodus lasting 13-49 days. The P. vittata population from Tristan da Cunha departed, moulted and returned 15-17 days later than their counterparts from Gough Island. After breeding, both species showed a well-defined outward migration, with all moving west until the start of moult, except one P. vittata individual that moved east. Moulting was inferred from a marked reduction in the time spent in flight, which occurred shortly after arrival on the non-breeding grounds by both species (i.e. November– February for P. vittata and February–June for P. macgillivrayi). Moulting birds targeted specific areas with little overlap between species within the Argentine Basin. Both species briefly returned to their burrows after moulting. During the remainder of the non-breeding period both species were distributed more widely over the South Atlantic Ocean. Interspecific spatial segregation was observed for most of the tracking period, especially in core use areas. Pachyptila macgillivrayi spent more time flying, during both daylight and darkness, than P. vittata. Stable isotope signatures of prion flight feathers from tracked birds and additional samples from each population indicated that movements of tracked individuals were representative of the adult population, and were similar over years. Higher δ 15N values found in P. macgillivrayi feathers is consistent with the hypothesis that P. vittata, being the more specialist filter feeder, targeting copepods, should forage at a lower trophic level than the more generalist P. macgillivrayi. This is also consistent with the greater time in flight for P. macgillivrayi i.e. more time actively searching for food, rather than sitting on the water filtering. Across both species, bill width was positively correlated with the number of palatal lamellae with P. vittata having a wider bill containing more palatal lamellae and thus better equipped for filter feeding. Habitat analysis revealed biologically meaningful, speciesspecific preferences for distance from the breeding colony, chlorophyll-a and sea surface temperature, but not distance to seamount or for water depth. This study contributes to the growing number of studies tracking small petrels and provides information on the strategies employed by extremely similar and abundant seabirds, most notably allochrony for P. vittata and P. macgillivrayi, allowing ecological segregation as well as furthering the understanding of moult in prions. The findings of this thesis advance the knowledge of the ecology of these poorly studied species of prions.